Management of Pelvic Ring Injury Patients With Hemodynamic Instability - Marmor, Meir; El Naga, Ashraf N.; Barker, Jordan; Matz, Jacob; Stergiadou, Styliani; Miclau, Theodore (Frontiers in Surgery, 2020)
Pelvic ring injuries are among the most difficult injuries to deal with in orthopedic trauma. When these injuries are accompanied by hemodynamic instability their management becomes significantly more complex. A methodical assessment and expeditious triage are required for these patients followed by adequate resuscitation. A major triage decision is whether these patients should undergo arterial embolization in the angiography suit or prompt packing and pelvic stabilization in the operating room. Patient characteristics, fracture type and injury characteristics are taken into consideration in the decision-making process. In this review we discuss the acute evaluation, triage and management of pelvic ring injuries associated with hemodynamic instability. An evidence based and protocol driven approach is necessary in order to achieve optimal outcomes in these patients.